The effect of geologic conditions on the fire behavior of tunnels considering soil-structure interaction. (April 2022) - Hua, Nan; Tessari, Anthony; Elhami Khorasani, Negar
Highlights: The fire performance of reinforced concrete tunnel lining sections is studied. Four ground conditions ranging from shallow soft soil to deep rock are included. The fire performance of lining sections is simulated during heating and cooling. Fire-induced deformations and internal forces in the tunnel sections are compared. Effect of temperature-dependent soil properties on tunnel fire behavior is studied. Abstract: This paper compares the fire performance of bored reinforced concrete tunnel lining sections under four ground conditions, ranging from shallow soft soil to deep rock. The fire performance is analyzed using a verified finite element beam-spring model. The investigated lining sections are adopted from realistic high-profile tunnels. A series of analyses are conducted to evaluate the performance of tunnel sections under a wide range of fire scenarios and ground conditions. First, the fire behavior of the four tunnel sections under the RABT-train fire curve is simulated during heating and cooling, and the results are reported in terms of structural performance and sectional stress–strain response. Second, the time to reach a limit state for the four tunnel sections is quantified under an extended RWS fire curve. Finally, a simplified methodology is proposed to include temperature-dependent soil properties, including the heat induced excess pore pressure and change in subgrade reaction modulus under elevated temperatures. The influence of temperature-dependent soil properties on the structural fire performance of a shallow tunnel section in soft clay is studied. The results show that bored reinforced concrete linings could experience significant irrecoverable damage from exposure to major fires. The moderate-depth tunnel section in soft soil and the deep tunnel section in high lateral pressure rock are the two critical cases, due to the large deformations and high internal forces, respectively. The importance of including temperature-dependent soil properties in tunnel fire analyses is demonstrated.